BIOACTIVITY, PHYSICOCHEMICAL AND ANTIMICROBIAL PROPERTIES OF VINEGAR MADE FROM PERSIMMON (DIOSPYROS KAKI) PEELS - Bayram, Yuksel; Ozkan, Kubra; Sagdic, Osman (YILDIZ TECHNICAL UNIV, 2020)
Persimmon (Diospyros kaki) wastes are defined as a new alternative source for vinegar production. This approach enables the utilization of the persimmon peels which are generally thrown during the consumption or processing of the fruit. The present study investigated total phenolic compound (TPC), total flavonoid compound (TFC), antioxidant capacities (DPPH) radical scavenging activity and the copper reducing antioxidant capacity (CUPRAC)) of persimmon peel vinegar. Additionally, the antimicrobial and some physicochemical properties of the persimmon peels vinegar were evaluated. TPC, TFC were 292.28 mg gallic acid equivalent (GAE)/L and 17.36 mg catechin equivalent (CAE)/L, for persimmon vinegar, respectively. In terms of antioxidant activity, persimmon peels vinegar extracts had 225.44 mg Trolox equivalent (TE)/L for DPPH assay, and 589.07 mg TE/L for CUPRAC assay. Titratable acidity, pH and Brix values of vinegar samples were found as 4.5%, 3.64%, and 1.2%, respectively. The vinegar showed a well antimicrobial effect. Generally, upon increasing the extract concentration, the inhibition zone was also increased, and the highest inhibition zone was observed at direct (100%) extract concentration applied against Escherichia coli for antibacterial activity and the highest inhibition zone was observed at direct (100%) extract concentration applied against Aspergillus niger for antifungal activity. This study suggested that especially in vinegar production, food waste might be evaluated and also, this vinegar has health-promoting qualities and might be a competitive product in the commercial market.
Keywords: Diospyros kaki Peels; vinegar; waste; antioxidant; antimicrobial; ANTIOXIDANT ACTIVITY; TOTAL PHENOLS; BY-PRODUCTS; POLYPHENOLS; CAPACITY; INDEX; WINE; Engineering